Improving WHO’s understanding of WHO guideline uptake and use in Member States: a scoping review - Kiran Saluja; K. Srikanth Reddy; Qi Wang; Ying Zhu; Yanfei Li; Xiajing Chu; Rui Li; Liangying Hou; Tanya Horsley; Fred Carden; Kidist Bartolomeos; Janet Hatcher Roberts (Health Research Policy and Systems, 2022)
Abstract Background WHO publishes public health and clinical guidelines to guide Member States in achieving better health outcomes. Furthermore, WHO’s Thirteenth General Programme of Work for 2019–2023 prioritizes strengthening its normative functional role and uptake of normative and standard-setting products, including guidelines at the country level. Therefore, understanding WHO guideline uptake by the Member States, particularly the low- and middle-income countries (LMICs), is of utmost importance for the organization and scholarship. Methods We conducted a scoping review using a comprehensive search strategy to include published literature in English between 2007 and 2020. The review was conducted between May and June 2021. We searched five electronic databases including CINAHL, the Cochrane Library, PubMed, Embase and Scopus. We also searched Google Scholar as a supplementary source. The review adhered to the PRISMA-ScR (PRISMA extension for scoping reviews) guidelines for reporting the searches, screening and identification of evaluation studies from the literature. A narrative synthesis of the evidence around key barriers and challenges for WHO guideline uptake in LMICs is thematically presented. Results The scoping review included 48 studies, and the findings were categorized into four themes: (1) lack of national legislation, regulations and policy coherence, (2) inadequate experience, expertise and training of healthcare providers for guideline uptake, (3) funding limitations for guideline uptake and use, and (4) inadequate healthcare infrastructure for guideline compliance. These challenges were situated in the Member States’ health systems. The findings suggest that governance was often weak within the existing health systems amongst most of the LMICs studied, as was the guidance provided by WHO’s guidelines on governance requirements. This challenge was further exacerbated by a lack of accountability and transparency mechanisms for uptake and implementation of guidelines. In addition, the WHO guidelines themselves were either unclear and were technically challenging for some health conditions; however, WHO guidelines were primarily used as a reference by Member States when they developed their national guidelines. Conclusions The challenges identified reflect the national health systems’ (in)ability to allocate, implement and monitor the guidelines. Historically this is beyond the remit of WHO, but Member States could benefit from WHO implementation guidance on requirements and needs for successful uptake and use of WHO guidelines.